1972
DOI: 10.1111/j.1748-1716.1972.tb05239.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Secretin, Cholecystokinin and Caerulein on Gastric Secretion in Response to Sham Feeding in Dogs

Abstract: SJODIN, L. Effects of secretin, cholecystokinin and caerulein on gastric secretion inresponse to sham feeding in dogs. Acta physiol. scand. 1972. 85. 99-109. Secretin (0.75-3.0 U/kg/h) did not regularly inhibit the acid secretory response to 10 min of sham feeding to a significant degree in 3 dogs with intact antrum. Cholecystokinin (0.75-5.0 U/kg/h) and caerulein (0.06-0.30 p/kg/h) tended to increase acid output after sham feeding in these dogs. In antrectomized dogs the response to sham feeding was marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Ingestion of fat also inhibits the motility in the digestive tract. Moreover, as already indicated, in dogs low doses of CCK potentiates the acid secretion caused by vagal stimulation (Sjodin, 1972). Fat, like neurotensin, is also known to inhibit the rnyoelectric motor complexes in the small intestine (Al-Saf€ar & Rosell, 1981;Nebel & Castell, 1972;Thor et al, 1980).…”
Section: Neurotensin As a Hormonementioning
confidence: 89%
See 2 more Smart Citations
“…Ingestion of fat also inhibits the motility in the digestive tract. Moreover, as already indicated, in dogs low doses of CCK potentiates the acid secretion caused by vagal stimulation (Sjodin, 1972). Fat, like neurotensin, is also known to inhibit the rnyoelectric motor complexes in the small intestine (Al-Saf€ar & Rosell, 1981;Nebel & Castell, 1972;Thor et al, 1980).…”
Section: Neurotensin As a Hormonementioning
confidence: 89%
“…Similarly, if the pouch is vagally denervated (Heidenhain pouch) neurotensin does not inhibit the gastric acid secretion (Anderson et a/., 1980). Chole-cystokinin in low doses inhibits the gastrin-induced acid secretion from vagally denervated pouches, but potentiates the acid secretion caused by vagal stimulation (Sjodin, 1972). Secretin effectively inhibits the gastric acid sEcretion in denervated, but less so in innervated, fundic pouches (Sjodin & Miura, 1974).…”
Section: Gastric Acid Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…8], It is of interest that secretin, which resembles glucagon in its amino acid sequence and in some aspects of its physiological activity, fails to inhibit food-stimulated gastric secretion from the Pavlov pouch [12]. However, secretin was tested in a relatively small dose and it is not excluded that if this hormone were used in a dose equal to that used for glucagon in the present study, inhibition might be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Of these agents, the best studied is cholecystokinin (CCK). The ability of CCK to decrease food intake was first demon strated in the early seventies by Sjodin [17] in dogs and Gibbs et al [18] Much controversy has existed concerning whether CCK truly produces satiety or whether the decrease in food intake it produces is an aversive phenomenon. Bil lington et al [21], using the differential satiety method, clearly showed that CCK was not aversive in rats.…”
Section: The Peripheral Satiety Systemmentioning
confidence: 99%